Type and Density of Zooplankton in The Sepinang Lake Pangkalan Serik Village, Siak Hulu Sub District, Kampar District, Riau Province - D Kusumawati, Yuliana; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract There were several human activities around the Sepinang Lake that contribute the input of organic and anorganic matter and thus influence the type and density of zooplankton. To understand the types and density of zooplankton in the Sepinang Lake, a research has been carried out in March-April 2018. There were three sampling points, namely in the inlet, in the middle of the lake, and in the end of the lake. In each sampling point, the water was sampled from the surface and 2 Secchi depth. Sampling were conducted 3 times, once/week. Water quality parameters measured were temperature, transparency, dissolved oxygen, pH,nitrate and phosphate. Results shown that there were 19 species of zooplankton present and they were belonged to 7 classes, namely Cladocera (2 species), Monogononta (9 species), Crustacea (3 species), Copepod (1 species), Ciliate (2 species), Sarcodina (1 species) and Eurotatoria (1 species). The zooplankton density in the Sepinang Lake was 2,448-3,808organisms/L.The most commontype of zooplankton present in the Sepinang Lake was Ciliate.Water quality parameter values are as follow,  temperature was 30.7-32.0oC, transparency was 49.3-62.8 cm, dissolved oxygen was 4.22-5.58 mg/L, pH was 5.33-5.60, CO2was 9.32-15.98 mg/L, nitrate was 0.07-0.23 mg/L and phosphate was 0.09-0.28 mg/L. Based on the type and density of zooplankton present, it can be concluded thatthe Sepinang Lake can be categorized as oligothropic. Keywords : Kampar River, Oxbow Lake, Eutrophic, Ciliate.